Das Schweben und die Form. Angela Krauß’ Erzählkunst - Eke, Norbert Otto (Neue deutsche Literatur)

„Was wollen Sie? Die Absolution?“ Opfer- und Täterprojektionen bei Maxim Biller - Eke, Norbert Otto (Zeitschrift für deutsche Philologie. Beiheft 11: Deutsch-jüdische Literatur der neunziger Jahre. Die Generation nach der Shoah. Hg. von Sander L. Gilman und Hartmut Steinecke)
Angabe zum Ort: Berlin

Non-typical measurements during an isokinetic training session after ACL-reconstruction - Baumeister, Jochen; Weiss, M (Sportverl Sportschad)

Zur Berechenbarkeit reeller geometrischer Probleme - Ziegler, Martin
Die Implementierung von Algorithmen zur Lösung geometrischer Probleme im Euklidischen Raum (z.B. Berechnung der konvexen Hülle oder des Durchschnitts zweier Polyeder) stellt sich oftmals als hochgradig nichttrivial heraus. Ob und unter welchen Voraussetzungen die verursachenden numerischen Instabilitäten überhaupt ini den Griff zu kriegen oder vielmehr dem Problem inhärent sind, untersucht diese Arbeit in einem auf Turing zurückgehenden Rechenmodell. Im Gegensatz zu algebraischen Ansätzen geht jenes nicht von der Verfügbarkeit exakter Tests auf z.B. Gleichheit reeller Zahlen aus, sondern berücksichtigt die auf Digitalcomputern tatsächlich realisierbare Approximation durch rationale Zahlen. In diesem Rahmen werden beweisbar stabile Algorithmen zum Lösen linearer Gleichungssysteme, zur Matrix-Diagonalisierung und zur linearen wie nichtlinearen Optimierung präsentiert. Als wichtiges technisches Hilfsmittel dient ein neuer Berechenbarkeitsbegriff für reguläre unendliche Mengen reller Zahlen, der sich aus dem systematischen Vergleich verschiedener der Literatur entnommener ad-hoc Ansätze ergibt.

Computability on Regular Subsets of Euclidean Space - Ziegler, Martin (Mathematical Logic Quarterly (MLQ))

Point Location Algorithms of Minimum Size - Ziegler, Martin; Damerow, Valentina; Finschi, Lukas (Proceedings of the 14th Canadian Conference on Computational Geometry (CCCG'02))
Consider the classical point location problem: for a fixed arrangement of m hyperplanes and its induced partition of d-space report, upon input of some point, which face it lies in. With sufficient memory, this is easy to solve in logarithmic time O(log m). But how fast can algorithms (formalized as Linear Decision Trees) of *minimum* size be? The present work gives lower and upper bounds for the time complexity of point location under this constraint. They show that, in addition to m, the maximum number w of walls of a cell turns out to be a crucial parameter. We also consider a relaxation of the strict minimum-size condition allowing for constant factor overhead.

Computability of Linear Equations - Brattka, Vasco; Ziegler, Martin (Proceedings of the 2nd IFIP International Conference on Theoretical Computer Science)
Do the solutions of linear equations depend computably on their coefficients? Implicitly, this has been one of the central questions in linear algebra since the very beginning of the subject and the famous Gauß algorithm is one of its numerical answers. Today there exists a tremendous number of algorithms which solve this problem for different types of linear equations. However, actual implementations in floating point arithmetic keep exhibiting numerical instabilities for ill-conditioned inputs. This situation raises the question which of these instabilities are intrinsic, thus caused by the very nature of the problem, and which are just side effects of specific algorithms. To approach this principle question we revisit linear equations from the rigorous point of view of computability. Therefore we apply methods of computable analysis, which is the Turing machine based theory of computable real number functions. It turns out that, given the coefficients of a system of linear equations, we can compute the space of solutions, if and only if the dimension of the solution space is known in advance. Especially, this explains why there cannot exist any stable algorithms under weaker assumptions.

Bi-directional Coupling of Simulation Tools with a Walkthrough-System - Mueck, Bengt; Dangelmaier, Wilhelm; Fischer, Matthias; Klemisch, Wolfram (Simulation und Visualisierung)
Visualising is a method used to help experiencing and understanding causal cohesions in simulation processes. For this purpose, tools for visualising are already implemented in prevalent simulation systems. The user creates his simulation model and generates a 3-dimensional (2,5-dimensional) visualising by means of the simulation system. This helps examining the process which makes it easier for the viewer to understand it. Simulation tools usually only provide the opportunity for a unidirectional visualising. In a 3-dimensional surrounding the viewer can not implement an interaction with the simulation while the system is running. Though an interaction during the simulation run enables the user to gain a better understanding of causal cohesions. Solutions via HLA are sophisticated and therefore rather suited for extensive projects. We present a distributed system consisting of a commercial manufacturing simulation tool, a coupling module and a walkthrough system. The distributed system in conjunctions with the coupling module guarantees generality and a wide field of applications of the walkthrough system. Further it guarantees flexibility and selection of the specialized graphics hardware for the walkthrough system. A further contribution of this paper is the solution of the time synchronisation problem caused by simulation tool and walkthrough system.

Randomized Pursuit-Evasion in Graphs - Adler, Micah; Räcke, Harald; Sivadasan, Naveen; Sohler, Christian; Vöcking, Berthold (Proceedings of the 29th International Colloquium on Automata, Languages and Programming)
We analyze a randomized pursuit-evasion game on graphs. This game is played by two players, a hunter and a rabbit. Let G be any connected, undirected graph with n nodes. The game is played in rounds and in each round both the hunter and the rabbit are located at a node of the graph. Between rounds both the hunter and the rabbit can stay at the current node or move to another node. The hunter is assumed to be restricted to the graph G: in every round, the hunter can move using at most one edge. For the rabbit we investigate two models: in one model the rabbit is restricted to the same graph as the hunter, and in the other model the rabbit is unrestricted, i.e., it can jump to an arbitrary node in every round. We say that the rabbit is caught as soon as hunter and rabbit are located at the same node in a round. The goal of the hunter is to catch the rabbit in as few rounds as possible, whereas the rabbit aims to maximize the number of rounds until it is caught. Given a randomized hunter strategy for G, the escape length for that strategy is the worst case expected number of rounds it takes the hunter to catch the rabbit, where the worst case is with regards to all (possibly randomized) rabbit strategies. Our main result is a hunter strategy for general graphs with an escape length of only O (n log (diam(G))) against restricted as well as unrestricted rabbits. This bound is close to optimal since Ω(n) is a trivial lower bound on the escape length in both models. Furthermore, we prove that our upper bound is optimal up to constant factors against unrestricted rabbits.

Verteilter strukturierter Entwurf mechatronischer Systeme am Beispiel einer Steer-by-Wire-Lenkung - Nyenhuis, Markus; Rustemeier, Carsten; Dierkes, Ulrich (Fahrzeugschwingungen - Global Chassis Control)